Road Traffic Regulation Awareness, Attitude and Practice among Public Health Students: An Observational Study - Shahi, Shirshak; Singh, Sarswoti; Sharma, Bimala; Shakya , Sujata (Journal of Institute of Medicine Nepal, 2023)
Introduction Road traffic accidents (RTAs) are the leading causes of premature deaths in Low and Middle Income Countries (LMICs). Public health students are the special cadre of human resources for addressing public health issues in the community including RTAs. This study aimed to assess the awareness, attitude, and practice of public health students of Kathmandu Valley regarding road traffic regulations. Methods This was a cross-sectional study conducted among 395 undergraduate public health students of Kathmandu Valley using structured self-administered questionnaire via google forms. The study participants were selected through student networking and invitation through emails and phone calls. Descriptive statistics and inferential statistics: Mann-Whitney U test, Kruskall-Wallis H test, and spearman’s rank correlation were computed at 5% level of significance. Results Majority of the participants had knowledge on causes of RTAs, rule for seat belt and not using mobile phone while driving. However, few knew about the maximum penalty for driving without a license and correct side for pedestrians to walk. The median knowledge score on road traffic regulations was 11 out of 14, attitude score 7 out of 7, practice score for pedestrians 10 out of 12 and for drivers/riders 16 of 18. No significant association was found between knowledge and any socio-demographic variables. Knowledge was weakly correlated with attitude. Conclusion Majority of the participants had knowledge scores above average, while the attitude and practice percentages were higher. We found weak correlation of knowledge with attitude, and no correlation with practice. This indicates that there is still gap between knowledge and practice, which needs to be explored further.